Systematic Literature Review on Interest in Learning Entrepreneurship in Environmental Education - Pratiwi, Galuh Aulia; Zahroh, Ainun; Iswanto, Huddy; Aji, Wasis Jatmiko; Wardana, Ludi Wishnu; Narmaditya, Bagus Shandy (PT. EQUATOR SINAR AKADEMIA, 2024)
The problem of unemployment has become increasingly worrying in Indonesia recently. Innovation is needed in learning to increase interest in entrepreneurship among pupils and students. This research aims to look at research trends regarding entrepreneurial interest in the educational environment. The method used is a systematic literature review (SLR). Data was collected from several journal articles indexed by Sinta 1-4 and Scopus. From the established criteria, 50 relevant articles were found to be reviewed systematically. The results of this research show: 1) there is an increase in research on interest in entrepreneurship in the educational environment from 2019 to 2024. 2) The variables that often appear are learning models and entrepreneurship education. 3) Research on entrepreneurial interest in the educational environment covers many variables, with a main focus on college students and students. 4) The use of quantitative research methods still dominates in this research. Suggestions for future researchers are to consider various research methods for a more comprehensive understanding of entrepreneurial interest.